Efektivitas Model Pembelajaran Realistic Mathematics Education dalam Meningkatkan Pemahaman Konsep Matematika Siswa : Studi Literatur - Suci Hanifah Nahampun; Yeni Lupitasari Sinaga; Cindy Marito Habeahan; Roberkat Sardio Siahaan; Taruli Marito Silalahi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
This research aims to evaluate the effectiveness of the Realistic Mathematics Education (RME) learning model in improving students' understanding of mathematical concepts. The method used in this research is a literature study by analyzing various relevant literature sources. The results of this research show that the RME learning model can improve students' understanding of mathematical concepts by linking learning material to real life situations, increasing student involvement in the learning process, and encouraging students to think critically and creatively.